The life-cycle dynamics of wealth mobility - Richard Audoly; Rory McGee; Sergio Ocampo Díaz; Gonzalo Paz Pardo (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2024)
We use 25 years of tax records for the Norwegian population to study the mobility of wealth over people's lifetimes. We find considerable wealth mobility over the life cycle. To understand the underlying mobility patterns, we group individuals with similar wealth rank histories using agglomerative hierarchical clustering, a tool from statistical learning. The mobility patterns we elicit provide evidence of segmented mobility. Over 60 percent of the population remains at the top or bottom of the wealth distribution throughout their lives. Mobility is driven by the remaining 40 percent, who move only within the middle of the distribution. Movements are tied to differential income trajectories and business activities across groups. We show parental wealth is the key predictor of who is persistently rich or poor, while human capital is the main predictor of those who rise and fall through the middle of the distribution.
Keywords: 330